Novel immunomodulatory drugs and neo-substrates - Shaobing Gao; Shichao Wang; Yongping Song (BMC, 2020)
Abstract Thalidomide, lenalidomide and pomalidomide are immunomodulatory drugs (IMiDs) effective in the treatment of multiple myeloma, myelodysplastic syndrome (MDS) with deletion of chromosome 5q and other hematological malignancies. Recent studies showed that IMiDs bind to CRBN, a substrate receptor of CRL4 E3 ligase, to induce the ubiquitination and degradation of IKZF1 and IKZF3 in multiple myeloma cells, contributing to their anti-myeloma activity. Similarly, lenalidomide exerts therapeutic efficacy via inducing ubiquitination and degradation of CK1α in MDS with deletion of chromosome 5q. Recently, novel thalidomide analogs have been designed for better clinical efficacy, including CC-122, CC-220 and CC-885. Moreover, a number of neo-substrates of IMiDs have been discovered. Proteolysis-targeting chimeras (PROTACs) as a class of bi-functional molecules are increasingly used as a strategy to target otherwise intractable cellular protein. PROTACs appear to have broad implications for novel therapeutics. In this review, we summarized new generation of immunomodulatory compounds, their potential neo-substrates, and new strategies for the design of novel PROTAC drugs.